Analisis Penggunaan Metode Half Slab Terhadap Waktu Pelaksanaan Pembangunan Proyek Apartemen Caspian Tower Surabaya - Mochammad Choirul Effendi; Pandulu, Galih Damar; Jurnalisdel, Jurnalisdel (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2020)
The construction of vertical residential in Surabaya is one of the alternative supporting facilities and infrastructure to provide residential needs. Given that Surabaya is a center of trade, commercial, financial, and various economic activities including the governance administration of East Java. The construction of the Caspian Tower project uses the half slab precast system methods in the plate structure. The process of analysis in calculating plate structure refers to SNI-2847-2013 and SNI-7833-2012 to control the moment of the precast half slab. In the process of implementing this half slab method, will be comparisons with conventional systems in terms of implementation time and manpower requirements. Comparison of time and manpower requirements refers to field observation and interviews with parties directly related to the construction of this project The result of the analyses is of, D10-200 for half slab precast with the length of reinforcement overlap of 20 cm. D10 for the Hook Bar with the development length of 34 cm and a hook height of 4 cm with a distance from the edge of the precast 0.207x or 0.207y. D10-200 for plat insitu.,The result From the comparison of the two methods, the precast half slab method which is more efficient in its implementation time and Manpower with a difference of 13 days and 21 Manpower